Manajemen Risiko K3 pada Tahap Finishing Pekerjaan Arsitektur Proyek Konstruksi Gedung Gudang X Kota Surabaya : Penelitian - Fajrinia Putri Rudiansyah; Chofifah Ayu Kusumaningtyas; Yeshita Alifia Yuvianti; Denes Wara Ayu Puspita; Dani Nasirul Haqi; Lilis Sulistyorini; R. Azizah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Behind infrastructure development, the construction sector faces threats in the implementation of the Occupational Safety and Health Management System (SMK3). One area with high potential hazards is architectural work, which involves working at heights, the use of chemicals such as paint and glue, and the intensive use of electrical and mechanical equipment. This study aims to analyze occupational safety and health risk management in the finishing stage of architectural work on the X warehouse construction project in Surabaya City through the Identification Hazard Identification, Risk Assessment, and Opportunity (IBPR) method as stipulated in the Regulation of the Minister of Public Works and People's Housing No. 10 of 2021 concerning Guidelines for the Construction Safety Management System. The results of this study identified 6 hazards and 7 risks from the finishing stage of architectural work, including falling from heights, being hit by falling materials, and exposure to dust. Risk control in construction projects must be implemented through the provision of equipment according to capacity, the use of safe materials, worker training, and regular monitoring to improve workplace safety during the finishing stage of the warehouse construction project.